THE EQUITY OF ANTENATAL CARE STANDARD IN DIFFERENT AGES - Efvina Goemawati; Titis Widya Kristy (Universitas Airlangga, 2019)
Background: Antenatal care standard ensures the health of pregnant woman with early detection of risk factors, prevention and treatment provided by competent health practitioners. Health equality does not always mean improving the same service for everyone, but the services are provided according to everyone's needs.Aim: This research was to examine the antenatal standards based on patients’ needs in the Public Health Centre of Medokan Ayu.Methods: This research was observational by using cross-sectional design. The population in this study was 518 pregnant women who gave birth from June 2011 to May 2012 in the Primary Healthcare Center of Medokan Ayu. There were 88 mothers as samples obtained by a cluster random sampling.Results: This study determines the need for antenatal care standards can be fulfilled more for the age of <20 years and >30 years to avoid the high risk of maternal death and needs and equity based on the standards. There were no differences in the acceptance standard of antenatal care (5T and 7T) based on the age group between <20 years, 20-30 years, and> 30 years.Conclusions: Reproductive women need to recognize the importance of antenatal care. The availability and quality of antenatal care need to be further maintained by the healthcare providers, and they need to be more aware to the importance of antenatal care. Women in later reproductive period need to be aware of the prevailing risks in circumstances. Keywords: Equity, Antenatal care standard, Age.